1873 S.C. Rev. Stat. 710, ch. 138, § 7 - (:unkn) unknown (My University, 1873)
Whoever shall challenge another to fight at sword, pistol, rapier, or any other dangerous weapon, or who shall accept any such challenge, shall, for every offense, on conviction thereof, be deprived of the right of suffrage, and be disabled forever from holding any office of profit or honor under this State, and shall be imprisoned in the penitentiary for a term not exceeding two years, at the discretion of the Court.
Keywords: DUELING